Primary care registration of the mental health needs of patients treated at outpatient specialized services: results from a medium-sized city in Brazil - Carlos Alberto dos Santos Treichel; Ioannis Bakolis; Rosana Teresa Onocko-Campos (BMC, 2021)
Abstract Background Although matrix support seeks to promote integrating Primary Care with specialized mental health services in Brazil, little is known about the quantitative impact of this strategy on sharing cases between different levels of care. The aim of this study was to investigate the prevalence and factors associated with Primary Care registration of the mental health needs of patients treated at outpatient specialized services in a medium-sized city in Brazil with recent implementation of matrix support. Methods This is a document-based cross-sectional study conducted through an analysis of 1198 patients' medical records. Crude and adjusted associations with the outcome were explored using logistic regression. Results The prevalence of cases registered in Primary Care was 40% (n = 479). Evidence was found for associations between the outcome and the patients being over 30 years old, and referral by emergency or hospital services. There was conversely an inverse association between the outcome and status as a patient from the Outpatient Clinic or from the Psychosocial Care Center for psychoactive substance misuse. Conclusions Even with the provision of mechanisms for network integration, such as matrix support, our results suggest that more groundwork is necessary to ensure that sharing cases between Primary Care and specialized services is effective.